1976
DOI: 10.3382/ps.0550786
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Ochratoxicosis in Day-Old White Leghorns, Turkeys and Japanese Quail

Abstract: The comparative acute, oral toxicity of ochratoxin A for three day-old avian species is presented. The seven-day LD50 value for White Leghorns was calculated to be 3.4 +/-0.19 mgm./kg., for turkeys to be 5.9 +/- 0.72 mgm./kg., and for Japanese quail to be 16.5 +/- 0.56 mgm./kg., body weight. The dose-response curves are linear and parallel through one standard deviation on either side of the LD50 when log-dose is plotted against probit for survivors. It is suggested that the mechanism of action of ochratoxin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The changes in the liver and kidneys of broiler chicks fed OA in the present study are similar to those reported by Huff et al (1974Huff et al ( , 1975, Prior et al (1976), Dwivedi & Burns (1984a), Mohiuddin et al (1992) and Sandhu et al (1995). Gross and histopathological changes in the liver and kidneys recorded following S. Gallinarum infection were also similar to those reported by Chishti et al (1985), Kaushik et al (1986), Sandhu et al (1987), Kokosharov et al (1997), and Deshmukh et al (2005) in the liver and/or kidney of birds affected naturally or experimentally with S. Gallinarum.…”
Section: Discussionsupporting
confidence: 82%
“…The changes in the liver and kidneys of broiler chicks fed OA in the present study are similar to those reported by Huff et al (1974Huff et al ( , 1975, Prior et al (1976), Dwivedi & Burns (1984a), Mohiuddin et al (1992) and Sandhu et al (1995). Gross and histopathological changes in the liver and kidneys recorded following S. Gallinarum infection were also similar to those reported by Chishti et al (1985), Kaushik et al (1986), Sandhu et al (1987), Kokosharov et al (1997), and Deshmukh et al (2005) in the liver and/or kidney of birds affected naturally or experimentally with S. Gallinarum.…”
Section: Discussionsupporting
confidence: 82%
“…However, 1-day-old chicks are much more sensitive and a large single dose of ochratoxin A Downloaded by [Mercer University] at 19:55 02 November 2014 produced sr.riking lesions of acute nephrosis, complicated by visceral gout (Peckham et al, 1971). They found ochratoxin B to be considerably less toxic and Prior et al (1976) related mortality directly with dose. In young broiler chicks Huff et al (1974Huff et al ( , 1975) observed a significant increase in kidney weight with as little as 1 mg ochratoxin per kg food (half the amount necessary to reduce growth rate), but 4 mg/kg produced histologically discernible kidney changes, consisting of tubular dilation, epithelial cell swelling, oedema and proteinaceous casts.…”
Section: Ochratoxinsmentioning
confidence: 97%
“…In this respect, quails which are regarded as several times more resistant to ochratoxicosis than the chicken or turkey (Prior et al, 1976), having the most rapid metabolism of aflatoxin B1 (O'Brien, 1983) and being more resistant to aflatoxin than poults and goslings but less resistant than chickens (Arafa et al, 1981), could provide additional information in terms of a better understanding of aurofusarin action. However, there is no information available on the effects of aurofusarin on quails.…”
Section: Introductionmentioning
confidence: 97%